ASPEK-ASPEK HAK ATAS PENDIDIKAN SEBAGAI BAGIAN DARI HAK ASASI MANUSIA - Duwi Handoko; Tat Marlina; Ferry Asril (Ensiklopedia of Journal, 2021)
The purpose of this paper is to find out the regulation of the right to education in Indonesian law and the development of thinking in the field of the right to education as part of human rights in the economic, social and cultural fields in Indonesia. This type of research is normative legal research that specifically discusses human rights. Data analysis in this study was carried out systematically based on research problems described qualitatively. Thoughts on the right to education as part of human rights in the economic, social and cultural fields in Indonesia cannot be separated from the rules of international law related to the right to education. The right to obtain education in an international environment is seen as an international legal rule (agreement) so that the state's obligation to meet the educational needs of its citizens is a contractual obligation. Failure to carry out this obligation would be a violation of the agreement so that the limits of state liability and the implementation mechanism depend on the agreement in question.